2010
DOI: 10.1517/17425247.2010.485608
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic nebulization platforms for pulmonary drug delivery

Abstract: Recent advances in ultrasonic nebulization technology demonstrate significant potential for the development of smart, portable inhalation therapy platforms for the future. Nevertheless, there remain considerable challenges that need to be addressed before such personalized delivery systems can be realized. These have to be addressed across the spectrum from fundamental physics through to in vivo device testing and dealing with the relevant regulatory framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 107 publications
1
67
0
2
Order By: Relevance
“…Omitting the PCL excipient, showed that nanoparticles of insulin and BSA could be fabricated using SAW atomization of buffered deionized water solutions of these biological proteins at a concentration from 0.5 to 2 mg=m'. They also showed if the SAW atomized drops were prevented from evaporation, as would happen in inhalation, for example (Groneberg et al, 2003;Yeo, Friend et al, 2010), the nebulized drops would be around 3 m in diameter and therefore ideal for drug delivery via the pulmonary system. Because the SAW atomizer is capable of forming nebulized mists of these large molecules without damaging them, it may be a reasonable means to deliver such molecules as a portable device.…”
Section: Atomizationmentioning
confidence: 99%
“…Omitting the PCL excipient, showed that nanoparticles of insulin and BSA could be fabricated using SAW atomization of buffered deionized water solutions of these biological proteins at a concentration from 0.5 to 2 mg=m'. They also showed if the SAW atomized drops were prevented from evaporation, as would happen in inhalation, for example (Groneberg et al, 2003;Yeo, Friend et al, 2010), the nebulized drops would be around 3 m in diameter and therefore ideal for drug delivery via the pulmonary system. Because the SAW atomizer is capable of forming nebulized mists of these large molecules without damaging them, it may be a reasonable means to deliver such molecules as a portable device.…”
Section: Atomizationmentioning
confidence: 99%
“…53,54 Although better deposition, compared to jet nebulizer, has been reported with newer models, 53 the impression is that the ultrasonic nebulizer technology requires more development in order to achieve wider acceptance. 55 For example, the versatility of ultrasonic nebulizers in clinical practice may be restricted due to heating issues. In contrast to jet nebulizers (in which drug solutions cool during aerosolization), ultrasonic nebulizers tend to heat up solutions as much as 20°C over 6 min.…”
Section: Nebulizersmentioning
confidence: 99%
“…1 Representation of the principles of a typical jet nebulizer [26]. Jet (or pneumatic) nebulizers effectively suck drug-containing liquid into the jet nozzle via high-velocity air flows.…”
Section: Nebulizer Device Characteristicsmentioning
confidence: 99%
“…2 Representation of a vibrating mesh nebulizer [26]. Aerosol droplets are generated by a perforated vibrating mesh which can be customized to the physicochemical properties of a particular drug formulation by altering size, number and distribution of the holes, power input, and frequency to the piezo element [28].…”
Section: Nebulizer Device Characteristicsmentioning
confidence: 99%